Quantitative rise in intraocular pressure in patients undergoing robotic surgery in steep Trendelenburg position: A prospective observational study - Nitesh Goel; Itee Chowdhury; Jitendra Dubey; Amit Mittal; Soumi Pathak (Wolters Kluwer Medknow Publications, 2020)
Background and Aims: Raised intraocular pressure (IOP) is one of the known causes of anterior ischemic optic neuropathy. In the case of robotic urological-gynecological surgeries, patient is kept in steep Trendelenburg supine-lithotomy position. Aim of this study was to observe the quantitative rise in IOP in steep Trendelenburg position (>45°) in robotic-assisted prostatectomy and hysterectomy. Material and Methods: After institutional ethical clearance and written informed consent, 100 patients undergoing robotic surgeries in steep Trendelenburg position were recruited for the study. IOP was measured at different time intervals in steep Trendelenburg position using Schiotz tonometer: Post intubation (T1), post pneumoperitoneum (T2), post steep Trendelenburg (T3), and rest readings were taken 30 min apart. T9 was taken 10 min after patient is made supine and parallel to the ground. Mean arterial pressure (MAP), positive inspiratory pressure (PIP), and end-tidal carbon dioxide (EtCO2) values were recorded at different time points. Descriptive analysis, linear regression analysis, and Freidman's nonparametric tests were used to analyze the results. Results: Ninety-five patients were included for statistical analysis as five patients were excluded due to intraoperative interventions leading to alteration of results. Mean IOP at T1 was 19.181/18.462 mmHg in L/R eye. A gradual rise in IOP was observed with every time point while patient was in steep Trendelenburg position which reverts back to near normal values once the patient is changed to normal position 21.419/20.671: Left/right eye in mm of Hg. Uni and multiple regression analysis showed insignificant P value, thus no correlation between MAP, PIP, and EtCO2 with IOP. Conclusion: Steep Trendelenburg position for prolong duration leads to significant rise in intraocular pressure.